2023
DOI: 10.2478/aoas-2022-0057
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds, antibiotics and heavy metals: Effects on the intestinal structure and microbiome of monogastric animals – a non-systematic review

Abstract: The intestinal structure and gut microbiota are essential for the animals‘ health. Chemical components taken with food provide the right environment for a specific microbiome which, together with its metabolites and the products of digestion, create an environment, which in turn is affects the population size of specific bacteria. Disturbances in the composition of the gut microbiota can be a reason for the malformation of guts, which has a decisive impact on the animal‘ health. This review aimed to analyse sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 232 publications
0
6
0
Order By: Relevance
“…Additionally, algae can have prebiotic effects by promoting the growth of beneficial gut bacteria. This contributes to a healthier gut microbiome, essential for efficient digestion and overall health [54,55]. Algae are also rich in antioxidants, including polyphenols and carotenoids, which help protect digestive tract cells from oxidative damage, maintain gut health, and reduce inflammation, thereby alleviating digestive discomfort [56].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, algae can have prebiotic effects by promoting the growth of beneficial gut bacteria. This contributes to a healthier gut microbiome, essential for efficient digestion and overall health [54,55]. Algae are also rich in antioxidants, including polyphenols and carotenoids, which help protect digestive tract cells from oxidative damage, maintain gut health, and reduce inflammation, thereby alleviating digestive discomfort [56].…”
Section: Discussionmentioning
confidence: 99%
“…Among natural food components, compounds with prebiotic activity have a positive effect on the microbiota. This group includes indigestible oligosaccharides, whose positive influence on the structure of the gut microbiota and overall health has been proven in numerous studies [ 2 , 10 , 11 ]. However, recent studies have also shown that polyphenols, which are secondary metabolites produced by plants, exhibit prebiotic properties.…”
Section: The Impact Of Gut Microbiota On Oestrogen Synthesismentioning
confidence: 99%
“…Prebiotics, on the other hand, are food components that positively impact well-being and health by selectively stimulating the growth and/or activity of gut microbiota, thereby also positively influencing the gut structure [ 8 ]. This group includes indigestible oligosaccharides, and their positive effects on gut microbiota structure and health have been demonstrated in numerous studies [ 2 , 9 , 10 ]. However, recent research has shown that polyphenols, which are likely the most important secondary metabolites produced by plants, also exhibit prebiotic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal nutrition is important in the healthy physical and mental development of mammals and has long-term effects evident later in life 10 , 11 . ACR is often consumed unknowingly and thus ACR dietary intake is difficult to assess 12 – 14 .…”
Section: Introductionmentioning
confidence: 99%